A self-rectifying unipolar HfOx based RRAM using doped germanium bottom electrode - Liu, W. J. (2013)
A self-rectifying unipolar RRAM based on HfOx dielectrics using highly doped n-type germanium substrate as the bottom electrode is proposed for the first time. The RRAM cells exhibit a stable unipolar resistive switching behavior. Owning to Schottky barrier between defect states in HfOx layer and n-Ge substrate, RRAM cells possess a self-rectifying behavior in LRS which eliminates the read-out errors induced by leakage current paths in cross-bar array structure. The demonstrated RRAM device shows high ON/OFF ratio (>5 × 102 @ 0.5 V), and its effective Schottky barrier height is also addressed. The demonstrated HfOx-based RRAM devices provide a promising candidate as non-volatile memory devices using Ge-based technology.